STRATEGIC MANAGEMENT LEADERSHIP IN THE IMPLEMENTATION OF DIGITAL MARKETING IN EDUCATIONAL INSTITUTIONS - Endrik Sugianto; Ibrahim Bafadal; Sultoni Sultoni (LP2M IAI Al-Khairat Pamekasan, 2026)
The development of digital technology has transformed marketing practices across various sectors, including educational institutions. The main issue addressed in this study is how strategic management leadership plays a role in optimizing the implementation of digital marketing in educational institutions. This study aims to analyze the role of strategic leadership in designing, implementing, and evaluating effective digital marketing strategies. The research method used is a qualitative approach through literature study and descriptive analysis of relevant scientific sources. The findings indicate that strategic management leadership plays a crucial role in determining the direction of digital marketing policies, enhancing institutional competitiveness, and building a positive image through the use of social media, websites, and other digital platforms. Furthermore, the success of digital marketing is highly influenced by the leader’s ability to adapt to technological changes, manage human resources, and foster continuous innovation. In conclusion, visionary and adaptive strategic leadership is a key factor in the successful implementation of digital marketing in educational institutions to increase attractiveness and ensure institutional sustainability in the digital era.